2011
DOI: 10.1007/s00520-011-1217-6
|View full text |Cite
|
Sign up to set email alerts
|

Palliative sedation at the end of life at a tertiary cancer center

Abstract: PS is an important intervention in the management of terminal disease by a consulting palliative care team. Improved collaboration and communication between the hospital staff and the PCCT should be offered to meet patients' needs when PS is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
2

Year Published

2013
2013
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 45 publications
1
26
1
2
Order By: Relevance
“…14 A study by Caraceni and colleagues, published after April 2011, confirmed the result of Miccinesi and colleagues by showing that palliative sedation was more frequently indicated in male patients (odds ratio 3.2; 95% confidence interval 1.5-7.0). 15 In general, women have different trajectories at the end of life than men. Indeed, women tend to live longer and have a different disease epidemiology and are more likely to receive care in a nursing home at the end of life, which may lead to different medical end-of-life decisions.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…14 A study by Caraceni and colleagues, published after April 2011, confirmed the result of Miccinesi and colleagues by showing that palliative sedation was more frequently indicated in male patients (odds ratio 3.2; 95% confidence interval 1.5-7.0). 15 In general, women have different trajectories at the end of life than men. Indeed, women tend to live longer and have a different disease epidemiology and are more likely to receive care in a nursing home at the end of life, which may lead to different medical end-of-life decisions.…”
Section: Treatmentmentioning
confidence: 99%
“…4 The frequency of palliative sedation has been reported to range from 2.5% to 64% among terminally ill patients. 14,15 This wide range likely reflects variations in the definition of the term and differences in culture and clinical settings.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, the duration of PS may be unusually longer. In this case, PS lasted for 39 days, whereas it is found in the literature to reach an average of less than 5 days [6][7][8] .…”
Section: Discussionmentioning
confidence: 60%
“…Misunderstandings concerning probable life-shortening effects of PS and differentiating PS from euthanasia (2)(3)(4) may have led to barriers and concerns in the application of PS in clinical practice. Rather inconsistent treatment regimens and research findings on the definition (1,(5)(6)(7)(8), incidence (9,10), indications (10)(11)(12), medication, and general professionals' attitudes (13)(14)(15)(16)(17)(18) toward PS were reported (9,15). Due to these uncertainties, the necessity for standardized guidelines was expressed (19).…”
Section: Introductionmentioning
confidence: 95%